Social policy : themes, issues and debates - Bochel, Hugh M. (Harlow, England : Pearson Prentice Hall, 2009)
The revised and extended edition provides a comprehensive introduction to contemporary British social policy, whilst acting as a complete learning resource for introductory courses and ultimately later modules of study.
Includes bibliographical references and index.
Keywords: United Kingdom -- Social policy